Activation of permanganate with hydrogen sulfite for enhanced oxidation of a typical amino acid. Issue 12 (25th May 2019) - Liu, Cheng; Zhao, Meiqi; He, Siyuan; Cao, Zhen; Chen, Wei
ABSTRACT: Dissolved organic nitrogen (DON) has drawn more attention from research into drinking water treatment because of its potential to form nitrogenous disinfection byproducts. Amino acids are important DON constituents that are difficult to remove by conventional water treatment. The permanganate/hydrogen sulfite (PM/BS) system, a novel oxidation process, is used to remove a typical amino acid, glutamate. The factors that affect removal mechanism and the degradation pathways were studied. The results show that the rates of DON and glutamate removal in the PM/BS system within 10 min were 55% and 90%, respectively. The optimum pH for glutamate degradation was 5, and the optimal dosages of KMnO4 and NaHSO3 were 1 mM and 5 mM, respectively. Activation ofMnO 4 − byHSO 3 − resulted in the oxidation of glutamate at very high rates. As shown by electronic spin resonance (ESR) experiments, Mn (III), SO 3 − ⋅, and OH were involved in the degradation process. The oxidation products suggest that most of the glutamate undergoes oxidation to ammonia nitrogen within 10 min, eventually forming N2 in the process. No evidence shows thatNO 3 − andNO 2 − formed during the entire process. High-performance liquid chromatography–mass spectrometry results reveal that glutamate degradation consists of two separate pathways involving Mn(III), SO 3 − ⋅, and OH, both of which convert –NH2 intoNH 4 + or directly to N2 . It can be indicated that nitrogenous disinfection by-products (N-DBPs) formation decreased in the degradation process, as shown by gas chromatograph detection.